PENGEMBANGAN MEDIA PEMBELAJARAN ANIMASI BERBASIS ANIMAKER PADA KELAS V TEMA 7 SUBTEMA 1 PERISTIWA KEBANGSAAN MASA PENJAJAHAN - Oktara Hari Purnama; Ratih Purnama Sari; Dendy Saeful Zen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Learning media is an important part of learning activities. At present the learning media used by teachers still use learning media which is less able to attract student learning interest because it only focuses on one learning media, printed books only. This study aims to determine the development of animaker-based learning media for students in class V theme 7 sub-theme 1 national events during the colonial period at SDN Cilebut 3 Bogor Regency and to determine the feasibility of animaker-based animated video media for the learning process. The method used in this study is the Research and Development (R&D) method with the ADDIE model. In this study, validation tests were carried out on several experts in the media, language, and material fields to develop and perfect animated video products using animakers for students. The results of the data from the validation of media experts are 97.5%, which means that the e-module is very feasible to try out. The linguist obtained 84% results, which means that it was declared very feasible and the results from material experts, 92.7%, which were stated to be very feasible for testing. As well as based on trials that have been carried out on fifth grade students as many as 39 students obtained a proper score to be used in the learning process of 88.30%, as well as trials that had been carried out on teachers of 96%, and the results of the evaluation test scores received an average score flat. an average of 82.20 students from KKM 75, got a presentation of student success in working on test questions of 92.30% which means that the E-Module product using flipbooks is very feasible to use in the learning process.